ANALYSIS OF THE SUCCESS OF ECONOMIC DEVELOPMENT IN SURABAYA IN THE ERA OF MAYOR TRI RISMAHARINI'S GOVERNMENT - Hadi, Akmal Firman; Enantya, Fionilla Belva Putri; Khakimah, Haidah (Laboratorium Riset Ekonomi, 2024)
The success of a country is influenced by many factors, one of which is economic development. Economic development is an indicator of the welfare and progress of a nation. Surabaya City is one of the cities in Indonesia in the East Java region that has been named a responsive and innovative government. The Surabaya city government is under the leadership of Tri Rismaharini in the 2010-2020 period. Mayor Tri Rismaharini showed various successes with indicators from the economic sector, development, to the environment. The research method used in this study is a descriptive qualitative method with a literature review approach. The results of this study show that several internal and external government factors greatly influence the development of good governance and have an impact on the success of government.